Satire in Modernism: A Comparative Study of T.S. Eliot's ‘The Love Song of J. Alfred Prufrock’ and Aldous Huxley's Crome Yellow - Ali Saeed, Alan (Zanco Journal of Human Sciences, 2023)
This article explores two stylistically very different texts of the modernist period, T.S. Eliot’s poem ‘The Love Song of J. Alfred Prufrock’ and Aldous Huxley’s novel Crome Yellow, through the comparative perspective of satire. It argues that they have more in common that may be at first supposed. The article argues in particular that the figure of Prufrock, the speaker of Eliot’s poem, provides the model for Denis Stone, the poetic protagonist of Crome Yellow as it is shown in a comparative reading of the two texts, seen in terms of their modernist historical context. Satire is often thought of as too didactic a literary mode to be amenable to modernism which places its emphasis instead on aestheticism and artistic experimentation and not providing lessons on how human being can be better. However, this is not always the case and Eliot’s self-satirising character Prufrock has important attributes that struck a chord with the generation, who like Huxley, lived through the horrors of World War One. The character of Prufrock with all his neurotic procrastination, failed romantic yearnings and doubts about his own masculinity came to inform Huxley’s own perspective on his protagonist Denis Stone in his novel and the article draws on Freud’s psychoanalytic explanation of neurosis to establish this. In conclusion, the article proposes that this comparative reading of ‘The Love Song of J. Alfred Prufrock’ and Crome Yellow in terms of satire requires us to see modernist satire as a novel, innovative, non-didactic form of satire, which in its tragi-comedy can be seen as directly implicated in British attitudes to both modernity and World War One.